Humans influence shrimp movement: a conservation behavior case study with "Shrimp Watching" ecotourism. Issue 2 (26th February 2021) - Hongjamrassilp, Watcharapong; Blumstein, Daniel T
Abstract: An increase in ecotourism adversely impacts many animals and contributes to biodiversity loss. To mitigate these impacts, we illustrate the application of a conservation behavior framework toward the development of a sustainable ecotourism management plan. In Ubon Ratchathani, Thailand, thousands of tourists annually come to see a unique mass migration of shrimps on land (referred to as "shrimp parading"). Preliminary work suggests that this tourism has negatively impacted the shrimps. To reduce tourism-related impacts we studied: 1) the decisions shrimps make when parading and 2) how shrimps respond to different light intensities and colors. We created an artificial stream and tested the conditions that influence parading by experimentally varying the presence of light and systematically manipulating water velocity (10, 60, and 100 cm/s). Additionally, we conducted an in situ experiment to study how shrimps respond to tourists' lights under three intensities (50, 400, and 9, 000 lux) and five colors (white, blue, green, orange, and red). We found most shrimps prefer to leave the river when it is dark and there is low water flow. Shrimps responded the least to red (λmax = 630 nm) and orange (λmax = 625 nm) light at 50 lux. These findings were used to develop a management plan by creating three different tourist zones, which maximize tourist needs and minimize the anthropogenic impacts on the shrimps. This work could be used as an example of the application of conservation behavior framework in developing management plan for sustainable ecotourism for other invertebrate taxa.